2009
DOI: 10.1111/j.1744-697x.2009.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing exclusion as a conservation measure in a South Australian temperate native grassland

Abstract: Many of South Australia's remnant temperate native grasslands are degraded by introduced livestock grazing. As a conservation measure, grazing was excluded from three 50 × 50 m exclosures in grazed native grassland. After 4 years, grazing removal had a noticeable effect on the grassland structure, increasing basal vegetation cover. Grazing removal had no significant effect on either native or exotic species richness, rather differences in richness changed as a result of interannual differences, such as the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Globally, overgrazing is one of the most important human disturbances, causing severe degradation of grasslands (Su et al, 2005;Liang et al, 2009) and reducing both productivity and resilience of grasslands (Zhou et al, 2011). Grazing exclusion (GE) is considered to be an effective approach to restore degraded grassland ecosystems, as well as to promote C sequestration (Akiyama & Kawamura, 2007;He et al, 2009;Souter & Milne, 2009;Wu et al, 2010;Qiu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, overgrazing is one of the most important human disturbances, causing severe degradation of grasslands (Su et al, 2005;Liang et al, 2009) and reducing both productivity and resilience of grasslands (Zhou et al, 2011). Grazing exclusion (GE) is considered to be an effective approach to restore degraded grassland ecosystems, as well as to promote C sequestration (Akiyama & Kawamura, 2007;He et al, 2009;Souter & Milne, 2009;Wu et al, 2010;Qiu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that exclusion of grazing did not produce changes in lowland grassland composition finds much support in the literature on grazing exclusion in southeastern Australian temperate grasslands; Zimmer et al (2010), Lewis et al (2008), Foreman (1996), Schultz et al (2014), McIntyre et al (2017) and Souter and Milne (2009) all found that species richness did not change significantly with grazing exclusion. By contrast, studies in more productive grasslands have shown that grazing exclusion will quickly (2–5 years) disadvantage inter‐tussock flora (e.g.…”
Section: Discussionmentioning
confidence: 67%
“…These findings are likely due to differences in the community composition among sites, with some conservation sites tending towards native shrub-dominated communities and others dominated by native tussocks. Removal of livestock leads to the recovery of dominant tussock species in talltussock grasslands, with a corresponding decline in native inter-tussock species in New Zealand (Rose and Platt 1992;Grove et al 2002;Mark and Dickinson 2003) and elsewhere (Souter and Milne 2009). Similarly in short-tussock communities, removal of livestock can lead to the recovery of shrub and inter-tussock species (Grove et al 2002).…”
Section: Livestock Removal and Native Plant Richnessmentioning
confidence: 99%
“…Also, while the effects of domesticated herbivores can be profound in the short term (Courchamp and Caut 2006), they can also take decades to play out, for example by influencing successional vegetation trajectories (Walker et al 2009). In ecosystems where domesticated herbivores have been introduced, grazing by livestock can alter community composition by reducing native plant richness (Walker and Lee 2002;Kimball and Schiffman 2003;Haarmeyer et al 2010), an effect that is often reversed with removal of livestock (Allcock and Hik 2004;Souter and Milne 2009). Also, grazing typically leads to short vegetation communities (Diaz et al 2007;May et al 2009), often with low shrub recruitment and decreased structural complexity (Lee et al 2010).…”
Section: Introductionmentioning
confidence: 99%